Avaliação do comprometimento cardiovascular de pacientes submetidos ao transplante hepático na infância - Ferreira, Michelle Loyola (2023)
Background: The use of immunosuppressive drugs in transplanted individuals seeks to avoid rejection of the transplanted organ, preserve its function and increase patient survival; however, adverse events can cause potentially negative repercussions on the cardiovascular system in the long term. Objective: To evaluate cardiovascular risk in individuals undergoing liver transplantation in childhood. Methods: cross-sectional study based on the analysis of 25 medical records of patients who underwent liver transplantation in childhood from 2003 to 2022 and continue to be followed up in outpatient care at the University Hospital of the Federal University of Sergipe in 2022. The following were evaluated: gender, age, body mass index (BMI), blood pressure, dyslipidemia, immunosuppressive drugs, electrocardiogram and Doppler echocardiography. Results: Female gender (56%); mean age at liver transplantation 1.96 ± 3.92 years; BMI (18.56 ± 3.64Kg/m2); systolic blood pressure SBP (104.32 ± 13.84 mmHg); DBP diastolic blood pressure (68.37 ± 9.37 mmHg); total cholesterol (140.3 ± 25.61 mg/dl); HDL-c (46.4 ± 18.25 mg/dl); LDL-c (72.30 ± 27.01 mg/dl); triglycerides (103.6 ± 47.69 mmol/l); use of tacrolimus (84%); electrocardiographic changes (28%); echocardiographic alterations (16%). The prevalence of transplant patients who developed systemic arterial hypertension was 32%. Conclusion: Patients after liver transplantation have a higher frequency of cardiovascular risk factors, especially systemic arterial hypertension, overweight and dyslipidemia.